2016
DOI: 10.1097/moh.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for acquired aplastic anemia

Abstract: Purpose of review There has been steady improvement in outcomes with allogeneic bone marrow transplantation (BMT) for severe aplastic anemia (SAA), due to progress in optimization of the conditioning regimens, donor hematopoietic cell source and supportive care. Here we review recently published data that highlight the improvements and current issues in the treatment of SAA. Recent findings Approximately one-third of AA patients treated with immune suppression therapy (IST) have acquired mutations in myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
0
21
0
7
Order By: Relevance
“…Allogeneic stem cell transplantation (SCT) can also be an option when the patient has a suitable donor [1]. Unrelated donor (URD) SCT is not usually recommended as first-line therapy for SAA because of higher transplantation-related mortality (TRM), including graft failure, graft-versus-host disease (GVHD), and infection compared with that of matched sibling donor (MSD) SCT [2,3]. However, a recent retrospective study from the European Society for Blood and Marrow Transplantation showed that the survival outcome of URD SCT was not statistically inferior compared to that of MSD SCT (5-year overall survival [OS], 78% versus 79%, respectively) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic stem cell transplantation (SCT) can also be an option when the patient has a suitable donor [1]. Unrelated donor (URD) SCT is not usually recommended as first-line therapy for SAA because of higher transplantation-related mortality (TRM), including graft failure, graft-versus-host disease (GVHD), and infection compared with that of matched sibling donor (MSD) SCT [2,3]. However, a recent retrospective study from the European Society for Blood and Marrow Transplantation showed that the survival outcome of URD SCT was not statistically inferior compared to that of MSD SCT (5-year overall survival [OS], 78% versus 79%, respectively) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bacigalupo et al [4] also showed that an HLA-mismatched donor or PB stem cells were both predictors of worse survival outcome and a higher incidence of GVHD. Furthermore, it has been generally suggested that HLA-mismatched donors and PB stem cells should be avoided and bone marrow (BM) is best stem cell source for URD SCT for SAA [3,6]. However, clinicians often encounter patients for whom an HLA-matched unrelated donor is unavailable or whose donors prefer to give PB rather than BM.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this, AA can occur secondary to the use of drugs such as cytostatic agents, chloramphenicol, carbamazepine, and phenytoin just as much as secondary to the exposure to environmental toxins such as benzene or exposure to ionizing radiation. AAs are graded by the degree of cytopenias with very severe AA, associated with a complete cessation of hematopoiesis, having a grave prognosis if untreated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Günümüzde halen geçerli olan rehberlerde akraba dışı tam uyumlu donörden transplantasyonların İST ile başarılı sonuç elde edilemeyen hastalarda uygulanacağı bildirilmektedir. Bununla birlikte, gerek İST ile ilgili komplikasyonlar, gerekse akraba dışı uyumlu donörden yapılan transplantasyon elde edilen başarılı sonuçlar nedeniyle; çocuklarda ve genç hastalarda akraba dışı uyumlu donörlerden yapılacak transplantasyonların ilk basamak tedavi olarak düşünülmesi gerektiği görüşü ağırlık kazanmaktadır (8)(9)(10). Son dönemlerde akraba dışı kord kanı ve haploidantik transplantasyonlar ile de başarılı sonuçların elde edildiği bildirilmektedir.…”
unclassified